Sistem Informasi Penilaian dan Monitoring Kinerja Aparatur Sipil Negara Kota Mataram - Lalu Muhammad Agung Hidayatullah; Royana Afwani; Budi Irmawati (Journal of Computer Science and Informatics Engineering (J-Cosine), 2019)
The Mataram municipal government is currently collecting ASNs Data. ASNs is employees working in the municipal government, which reach about 5500 people. As a consequent, the municipal have to spend budget to pay the ASNs salary. This salary is calculated based on ASNs position as well as then grade and class. The class and grade of the ASNs are evaluated based on their performance in completing their task. This evaluation is represented in such form called SKP (Sasaran Kerja Pegawai) that describe ASN work target and completeness. Currently, these forms are presented in Microsoft Excel that susceptible to errors. In this research, we develop a web-based system for the SKP for easy assessing the ASNs performance. Using this system, the ASNs evaluation were recorded in a database the baseline for future evaluation.